2022
DOI: 10.7717/peerj.12860
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability studies for tuber yield and yield attributes in Ethiopian released potato (Solanum tuberosum L.) varieties

Abstract: Information on the extent of genetic variability and association among quantitative traits are vital for any crop improvement program and the development of suitable selection strategies. Limited research has been carried out thus far on potato genetic variability and trait association. This study on genetic variability and association among quantitative traits was conducted to assess the extent of genetic variability among yield and agronomic traits to identify superior varieties for the breeding program. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The result was also found earlier by Rangare & Rangare [8]. Prajapati et al [9] Tessema et al [10] and Tessema et al [11].…”
Section: Resultssupporting
confidence: 86%
“…The result was also found earlier by Rangare & Rangare [8]. Prajapati et al [9] Tessema et al [10] and Tessema et al [11].…”
Section: Resultssupporting
confidence: 86%
“…Using different parts of the potato buds for direct planting, the emergence rate reached over 90%, among which the top bud emergence rate was as high as 98%, while the tail bud emergence rate was significantly lower than that of the bud block direct seeding treatment, showing a clear advantage of apical dominance. From the seedling stage to vigorous growth, the growth trend of the middle and tail bud treatments was delayed longer than that of the top bud, while the top bud direct cultivation treatment showed advantages such as vigorous growth, more leaves, strong photosynthetic ability, and higher yield, which is consistent with the principle that potato tubers have the strongest physiological and genetic potential at the top [19]. During the process of planting potato sprouts, ensuring the integrity of potato sprouts and their basal root primordia for planting is beneficial for the seedling growth rate, which is related to the occurrence and quantity of potato sprout root primordia [20].…”
Section: Discussionsupporting
confidence: 75%
“…In our study, high heritability was found for plant height, ear height, total leaves, anthesis day, silking day, ASI, number of ears per plant, grain yield, thousand grain weight, number of kernel rows per ear, and number of kernels per kernel row, while low heritability was found for maturity day and disease score (Table 6). Plant breeders can choose the direction of selection using high heritability values (Bartaula et al 2019), which will be used as a guide in selection (Tessema et al 2022). The low heritability values of observed traits suggest that environmental influences on their traits (Dochtermann et al 2019;Mustakim et al 2019).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%